Pengunaan Instagram @aslisuroboyo Informasi Masyarakat Surabaya - Sherlin Audina; Meithiana Indrasari; Eko Pamuji (LPPM Stikosa-AWS, 2023)
From the many information Instagram accounts in Surabaya, this study takes the object of the Instagram account @aslisuroboyo to see the effectiveness of the @aslisuroboyo account in meeting the needs of the people of Surabaya. The theory used is the theory of Uses and Gratification. The method used is descriptive qualitative method. Collecting data by interview and observation. The author takes the respondent journalist @aslisuroboyo and some followers on social media Instagram@aslisuroboyo. Based on the research conducted, theresults of thisstudy can be concluded that the Instagramaccount @aslisuroboyo fulfills the information of followers and the people of Surabaya. So it can be said that this research is effective.